Test-retest reliability of running economy and metabolic and cardiorespiratory parameters during a multistage incremental treadmill test in male middle- and long-distance runners - Brady, A. J.; Roantree, M.; Egan, B. (International Journal of Sport Nutrition and Exercise Metabolism, 2024)
This study investigated the test-retest reliability of running economy (RE) and metabolic and cardiorespiratory parameters related to endurance running performance using a multistage incremental treadmill test. On two occasions separated by 21-28 days, 12 male middle- and long-distance runners ran at 10, 11, 12, 13, and 14 km/hr for 8 min each stage, immediately followed by a ramp test to volitional exhaustion. Carbohydrate (10% maltodextrin solution) was consumed before and during the test to provide ~1 g/min of exercise. RE, minute ventilation (VE), oxygen consumption (VO2), carbon dioxide production (VCO2), respiratory exchange ratio (RER), heart rate (HR), ratings of perceived exertion (RPE), and blood glucose and lactate concentrations were recorded for each stage and at volitional exhaustion. Time-to-exhaustion (TTE) and peak oxygen consumption (VO2peak) during the ramp test were also recorded. Absolute reliability, calculated as the coefficient of variation (CV) between repeated measures, ranged from 2.3% to 3.1% for RE, whereas relative reliability, calculated as the intraclass correlation coefficient (ICC), ranged from .42 to .79. VE, VO2, VO2peak, VCO2, RER, and HR had a CV of 1.1%-4.3% across all stages. TTE and RPE had a CV of 7.2% and 2.3%-10.8%, respectively, while glucose and lactate had a CV of 4.0%-17.8%. All other parameters, except for blood glucose, were demonstrated to have good-to-excellent relative reliability assessed by ICC. Measures of RE, VO2peak, and TTE were reliable during this two-phase multistage incremental treadmill test in a cohort of trained and highly trained male middle- and long-distance runners.